O papel do estágio supervisionado na formação do professor de Espanhol/LE na licenciatura em Letras - Barreira, Vilma Lucia de Oliveira (2019)
This research has as general objective to verify the contributions of the Supervised Internship to the academic formation of the teacher of Spanish as a foreign language. It was developed in the city of Foz do Iguaçu, Paraná, through semi-structured interviews applied to eight professionals who undertook their initial training in a public higher education institution over the last decade. The proposal for its elaboration was based on the understanding that the Supervised Internship allows the students to put into practice the theoretical knowledge acquired throughout their undergraduate course. It is argued that there is no theory without practice, nor practice without theory. It is at this moment that the academic has the possibility to go to the "school ground floor", elaborate his lesson plans, have contact with the students, analyze the pedagogical practice developed by the lecturing professor and his own, by means of critical and reflexive analyses which will establish him as a teacher and that will be outlined in the final internship report. Through Supervised Internship, it is possible to experience the demands of the chosen profession, its bureaucratic aspects (elaboration of lesson plans, planning the teacher’s job, tests, homework, etc.) and especially orienting practice of the teaching and learning process. So as to better understand this context, the data collected, and the analyses weaved in the following chapters, the present study was based on the socio-historical-cultural perspective and on the identification of how Supervised Internship in Spanish is linked to the teaching and learning process of the future teacher, who needs to be continuously expanding his critical and reflexive sense, building himself as a professional committed to the education and effective teaching of the foreign language for which he is qualifying. Among the main authors studied are: Freire (1996), Tardif e Lessard (2008), Vygotsky (2010), Libâneo (2008), Nóvoa (2007, 2009), Bianchi (2005), Noffs e Espósito (2011), Pimenta e Lima (2012), Leffa (2005, 2016), Eres Fernández (2000), Kulikowski e Gonzáles (1999), Martínez-Cachero (2008), Paraquett (2009), Picanço (2003), among others. The results obtained in the research showed that the Spanish-speaking teachers entered the labor market, working in public or private institutions. They considered the hourly workload of the Supervised Internship carried out in the last year of graduation insufficient to effectively understand the dynamics that permeate the organization of the classroom and the teaching practice itself. They believe that they should start it in the third year of graduation, fulfilling a greater workload and having a closer follow-up of the university's guiding teacher and the class lecturer. Among the contributions of this training period, they highlighted the possibility of joining theory and practice, although they encountered difficulties being at the university and, simultaneously, planning and giving their lectures. There have been reports that indicated a good reception by the school and its managers and others have difficulties in starting and / or completing Supervised Internship. Regarding the students, different behaviors were evidenced that contemplated an active and committed participation, as well as disinterest to participate in the classes, a common situation in the school routine, especially when working with adolescents. Although school managers and in-service teachers understand the importance of Supervised Internship in the training of future Spanish-speaking teachers, and in all areas of undergraduate training, there is still a need for more effective joint work between school and university. Based on this data, it is suggested that the higher education institution researched review its curricular matrix and the way Supervised Internship is arrange